Light sintering of ultra-smooth and robust silver nanowire networks embedded in poly(vinyl-butyral) for flexible OLED - Dong Jun Lee (Nature Portfolio, 2018)
Abstract A conductive, uniform, and ultra-smooth flexible transparent composite film is produced by embedding silver nanowires (AgNWs) into poly(vinyl-butyral) (PVB) without pressure or high-temperature annealing. The adhesion of AgNWs was greatly improved by embedding them in PVB, and surface roughness and sheet resistance (Rs) improvements were achieved through the use of the intense pulsed light (IPL) method, which welds the interconnections among AgNWs in a short time without heat or pressure treatment. The sheet resistance of PVB/AgNWs with the IPL(PAI) composite film reaches 12.6 ohm/sq with a transmittance of 85.7% (at 550 nm); no clear changes in the sheet resistance are observed after a substrate bending and tape test, suggesting excellent flexibility. In the case of PAI, the change in sheet resistance was only 2.6% after a 2,000-bend test, and the resulting bending radius was less than 1 mm. When IPL was exposed to PVB/AgNWs, the figure of merit was 2.36 times higher than that without exposure. Finally, flexible OLEDs using PAI exhibited comparable or higher electroluminescent characteristics than other devices with well-known flexible electrodes—including indium-zinc-oxide on polymer plastic—which is a promising discovery for flexible optoelectronic applications.